Detección de cambios en la línea de costa en el municipio de Arboletes para los años 2001, 2010 y 2022 utilizando imágenes Landsat 7 y 8 (2023)
This work presents the analysis carried out on the dynamics of the coastline of the Municipality of Arboletes in the department of Antioquia from the processing of satellite images landsat 7 and 8 of the years 2001, 2010 and 2022. By digitizing the coastline of the years analyzed it was possible to calculate the change in this temporality.